Biology of Zygogramma Bicolorata Pallister on Parthenium hysterophorus Linn. under Laboratory Conditions - Ratna Bajracharya, Ajaya Shree; Bahadur Thapa, Resham; Bahadur K.C, Gopal; Baba Pradhan, Shree; Devi Ranjit, Jagat (Nepal Journal of Science and Technology, 2021)
Parthenium hysterophorus Linn. is one of the most aggressive, invasive weeds threatening natural and agricultural ecosystems in the world including Nepal. Augmentative release of host-specific, leaf feeding beetle, Zygogramma bicolorata Pallister (Coleoptera: Chrysomelidae) is one of the sustainable management approaches of parthenium weed. Successful mass rearing program requires knowledge on biology of Z. bicolorata for augmentative release. Thus, life cycle and biology of Z. bicolorata were studied in lab at 26±2 °C temperature and 70±10% relative humidity at NARC, Lalitpur, Nepal during March to September, 2016. The average incubation, larval and pupal periods of the insect were 4.33, 12.20, and 11.00 days, respectively. A single female could lay 1,837 eggs in 58.80 days oviposition period with 73.01% egg hatchability. The insect completed its life cycle in 108.40 and 105.50 days with adult longevity of 91.90 and 75.00 days for females and males, respectively. The average length of egg, pupa, adult female and male was 1.19 mm, 5.90 mm, 6.58 mm and 5.32 mm and breadth 0.51 mm, 3.74 mm, 3.94 mm and 3.20 mm, respectively. The average lengths of the first, second, third and fourth instar larvae were found 1.30 mm, 3.02 mm, 4.96 mm and 8.08 mm and breadth of 0.44 mm, 1.13 mm, 2.02 mm and 3.16 mm, respectively. These findings will help in mass multiplication of Z. bicolorata for biological control of parthenium weed.